The use of Kolb’s lenses to explore Social Sciences curriculum implementation in South African Schools : teachers’ perspective on pedagogy and content - Molapo, Karabo; Malatji, Khashane Stephen (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The social science curriculum serves as a key foundational subject to prepare learners who intend to further their studies by having History and Geography as specialized subjects. The success of the subject curriculum depends on the accomplishment and applicability of the subject policy objectives. However, despite the need to make the teaching and learning of the social science curriculum relevant, pedagogy and practice remain a challenge to meet the skills and values of the curriculum. Hence, this study explored teacher’s experiences of the Social Sciences curriculum in South African teaching and learning through Kolb’s experiential learning. Through Kolb’s experiential theory, the proponent emphasizes stages that need to be followed for content and pedagogic aspects of the subject. A qualitative approach with a case study design was adopted. Interpretive paradigm was used to look at teachers’ experience in the Social Science curriculum. Data was collected through individual semi-structured interviews with thirteen teachers. A thematic approach was used for data analysis. The findings of the study revealed that teachers lack pedagogies competencies for delivering Social Sciences teaching. The study concluded that teachers need to have knowledge and understanding of Social Sciences content to execute their key responsibility (teaching). Proper pedagogies such as small groups, discussion, and problem-solving should be incorporated into the subject to enable all learners within a band to understand the content taught. The study recommends Kolb’s stages of experiential learning be adopted to expose teachers to diverse ways that learners learn when executing a Social Science curriculum/lesson.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: Curriculum; Learning content; Pedagogy; Practice; Social Science; Teacher’s perspective; Teacher’s perspective; Learning content; Pedagogy; Social Science